Upaya Meningkatkan Hasil Belajar IPA dengan Menggunakan Model Inside Outside Circle dan Berbantuan Media Audio Visual Animasi - Ema Rosiana; Arif Supriyadi (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to improve the learning outcomes of science and describe the activities of students in the process of learning science through the Inside Outside Circle model with Audio Visual Animation media. The type of this research is class action research (PTK) with the subject of research all 10th-grade students of SDS Muhammadiyah Selat Kuala Kapuas male 10 people and female 17 people totaling 27 people. Data collection techniques in this study used observation and tests. Data analysis uses qualitative and quantitative data analysis. The results of this study indicate that: (1) Activity of fourth-grade students of SDS Muhammadiyah Straits of Kuala Kapuas in the process of learning science through assisting audiovisual animation media. Well categorized. This is evidenced in the first cycle categorized as good with the average value of the first cycle of 3.64 (2) There is an increase in science learning outcomes of the fourth-grade students of SDS Muhammadiyah Straits of Kuala Kapuas. This can be seen from the data from the research cycle II with an average value of 3.70 and 100% classical completeness